Evaluation of "Real-Time" Fatal Drug Overdose Surveillance by King County Medical Examiner's Office, Seattle, Washington. (22nd March 2023) - Harruff, Richard; Simpson, Celia M.; Gifford, Amy L.; Yarid, Nicole; Barbour, William L.; Heidere, Catherine
Abstract: To address the challenges in monitoring the continuously accelerating drug overdose epidemic, the King County Medical Examiner's Office in Seattle, Washington, instituted a "real-time" fatal drug overdose surveillance project, depending on scene investigations, autopsy findings, and in-house testing of blood, urine, and drug evidence collected from death scenes. Validation of the project's rapid death certification methodology from 2019 through 2021 was performed at the following 3 levels: blood testing, urine testing, and death certification, and for the following 4 drugs: fentanyl, opiate, methamphetamine, and cocaine. For blood testing, sensitivity ranged from 90% to 99%, and specificity ranged from 86% to 97%. For urine testing, sensitivity ranged from 91% to 92%, and specificity ranged from 87% to 97%. The positive predictive value for cocaine was poor for both blood testing (57%) and urine testing (72%). Of 1034 deaths, 807 were certified as overdose by rapid methodology, and 803 (99.5%) were confirmed by formal toxicology results. Manners of death were changed from accident to natural in 3 of 1034 cases (0.29%). Results of this study indicate that the rapid overdose surveillance methodology described in this study offers benefits to families and provides useful, timely information for responding law enforcement and public health agencies.